2015
DOI: 10.1073/pnas.1419264112
|View full text |Cite
|
Sign up to set email alerts
|

Control of bacterial exoelectrogenesis by c-AMP-GMP

Abstract: Major changes in bacterial physiology including biofilm and spore formation involve signaling by the cyclic dinucleotides c-di-GMP and c-di-AMP. Recently, another second messenger dinucleotide, c-AMP-GMP, was found to control chemotaxis and colonization by Vibrio cholerae. We have identified a superregulon of genes controlled by c-AMP-GMP in numerous Deltaproteobacteria, including Geobacter species that use extracellular insoluble metal oxides as terminal electron acceptors. This exoelectrogenic process has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 52 publications
6
114
0
Order By: Relevance
“…Thus, we demonstrate that cAG binding to the Gs1761 riboswitch aptamer disrupts terminator stem formation. Consistent with these results, an increase in full-length transcription with cAG was observed for another GEMM-Ib riboswitch (22). A key metabolic feature of the Geobacter genus is the ability to perform extracellular electron transfer.…”
supporting
confidence: 77%
“…Thus, we demonstrate that cAG binding to the Gs1761 riboswitch aptamer disrupts terminator stem formation. Consistent with these results, an increase in full-length transcription with cAG was observed for another GEMM-Ib riboswitch (22). A key metabolic feature of the Geobacter genus is the ability to perform extracellular electron transfer.…”
supporting
confidence: 77%
“…All sequenced Geobacter and Pelobacter species have at least one Hypr enzyme (SI Appendix, Fig. S9) and have riboswitch effectors that regulate genes in response to cAG (17,18). A second Hypr is predicted in G. sulfurreducens, but GSU1937 was not active in the biosensor-based screen (Fig.…”
Section: Whereas Previous Ggdef Enzymes Were Uniformly Assigned As Dgmentioning
confidence: 99%
“…We and others recently discovered that Geobacter, a genus of deltaproteobacteria, use cAG-sensing riboswitches to regulate genes associated with extracellular electron transfer (17,18), an extraordinary activity that involves bacterial colonization on metal oxide surfaces (19). We further showed that Geobacter sulfurreducens produces cAG (17), but the synthase enzyme remained a mystery.…”
mentioning
confidence: 97%
“…Some very rare riboswitch classes were discovered only because their representatives are very close derivatives of a more common riboswitch class, such as adenine or the 2 ′ -dG-I and -II riboswitches Weinberg et al 2017), all of which are variants of the vastly more common guanine riboswitch class initially discovered. Unfortunately, these close variants will remain hidden among the bioinformatics hits for a more prominent riboswitch class unless there are key distinctions, such as mutations to the ligand-binding core of the aptamer or gene associations that indicate a change in ligand specificity (Kellenberger et al 2015;Nelson et al 2015;Weinberg et al 2017).…”
Section: Introductionmentioning
confidence: 99%